Antimicrobial and demelanizing activity of Ganoderma lucidum extract, p-hydroxybenzoic and cinnamic acids and their synthetic acetylated glucuronide methyl esters - Heleno, Sandrina A. (2013)
Mushroom extracts or isolated compounds may be useful in the search of new potent antimicrobial agents. Herein, it is described the synthesis of protected (acetylated) glucuronide derivatives of p-hydroxybenzoic and cinnamic acids, two compounds identified in the medicinal mushroom Ganoderma lucidum. Their antimicrobial and demelanizing activities were evaluated and compared to the parent acids and G. lucidum extract. p-Hydroxybenzoic and cinnamic acids, as also their protected glucuronide derivatives revealed high antimicrobial (antibacterial and antifungal) activity, even better than the one showed by commercial standards. Despite the variation in the order of parent acids and the protected glucuronide derivatives, their antimicrobial activity was always higher than the one revealed by the extract. Nevertheless, the extract was the only one with demelanizing activity against A. niger. The acetylated glucuronide derivatives could be deprotected to obtain glucuronide metabolites, which circulate in the human organism as products of the metabolism of the parent compounds.